RUBCN as a novel prognostic biomarker and therapeutic target in breast cancer - Dong Dong Yang; Cheng Hao Liu; Sheng Qiu Jia; Ze Kuan Xue; Ming Ming Zhang; Rui Yang; Yong Zhou Huang; Xin Chun Zhao; Bao San Han; Sheng Dong Nie; Gui Lin Huang; Ji Xue Hou (PLoS ONE, 2026)
Analysis of autophagy-related gene expression data identified RUBCN as a novel biomarker influencing the pathogenesis and progression of breast cancer, underscoring its potential as a therapeutic target. We analyzed multiple breast cancer sample datasets using bioinformatics tools and databases. A consensus prognostic model was constructed and validated across several independent datasets to further examine its association with patient outcomes. A series of bioinformatics analyses focused on RUBCN were conducted, including expression profiling, independent prognostic evaluation, immune correlation analysis, and survival analysis. RUBCN expression was verified in breast cancer cell lines and clinical tissue specimens via Western blotting, quantitative real-time reverse transcription PCR, and immunohistochemistry. Functional assays, such as the Cell Counting Kit-8 assay, 5-ethynyl-2’-deoxyuridine incorporation assay, wound healing assay, and Transwell invasion assay, were employed to evaluate the effects of RUBCN knockdown on breast cancer cell proliferation and invasion. Autophagic activity, indicated by LC3 and P62 levels, was measured via Western blot in RUBCN-knockdown breast cancer cells with or without chloroquine treatment. Elevated expression of multiple autophagy-related genes was observed in breast cancer. The consensus prognostic model accurately predicted survival across multiple datasets, with RUBCN emerging as a key gene whose expression levels were significantly correlated with patient prognosis. Enrichment analysis indicated that RUBCN likely promotes breast cancer progression by regulating cell cycle and invasion processes. Further investigation revealed a negative correlation between RUBCN expression levels and immune cell infiltration, suggesting a potential role in mammary tumorigenesis through mediating immune evasion by suppressing immune cell infiltration. Immunohistochemical results confirmed upregulated RUBCN expression in carcinoma tissues. Knockdown of RUBCN was shown to suppress the proliferative and invasive abilities of breast cancer cells. Mechanistically, RUBCN knockdown impaired autophagic flux, as evidenced by altered LC3 and P62 levels upon chloroquine treatment. Together, these findings establish RUBCN as a promising therapeutic target in breast cancer. Future studies should emphasize in vivo functional validation using animal models and screen for targeted agents capable of modulating RUBCN expression or activity, thereby facilitating the development of innovative therapeutic strategies for breast cancer treatment.